Normalisasi EKG pada Pasien dengan Blok Berkas Cabang Kanan yang Dilakukan Pemacuan Ventrikel Kanan - Z Zainuddin; Yoga Yuniadi; Hardja Priatna; Dicky A Hanafi (Jurnal Kardiologi Indonesia, 2010)
Right ventricle apex (RVA) pacing bypasses the His-Purkinje system result-ing in left bundle branch block like pattern on surface EKG. In preexisting right bundle branch block (RBBB), pacing from certain location of RV might change the EKG pattern. We present two cases of normalization of QRS complex upon RV septal pacing in preexisting RBBB patients. The postulated mechanisms of the phenomenon is also proposed.